Penerapan Metode Talaqqi Dalam Hafalan Siswa Pada Ekstrakurikuler Tahfiz Di Madrasah Aliyah Swasta Al-Washliyah 68 - Sufyan; Ismail; Dina Pratiwi, Indah (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to determine the application of the talaqqi method in student memorization in the Tahfiz extracurricular program at Madrasah Aliyah Al-Washliyah 68. The research method used is qualitative with a descriptive approach. Research data was obtained from observations, interviews, and documentation. The results showed that the talaqqi method is applied in student memorization in the Tahfiz extracurricular program at Madrasah Aliyah Swasta Al-Washliyah 68 through several stages, namely: 1. Introduction 2. Core Activities 3. Closing. Through observation, interviews, and documentation, this study reveals the benefits of the application of the talaqqi method at Madrasah Aliyah Swasta Al-Washliyah 68, such as improving memorization, understanding, and faith. In addition, this study also identifies the constraints faced in the implementation of this method, especially related to human resources and student characteristics. The results of this study provide a significant contribution to the development of more effective tahfiz programs by considering the advantages and disadvantages of the talaqqi method